2006
DOI: 10.1902/jop.2006.060010
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Association Between Respiratory Diseases and Oral Health

Abstract: 1) There is fair evidence (II-2, grade B recommendation) of an association of pneumonia with oral health (odds ratio [OR]=1.2 to 9.6 depending on oral health indicators). 2) There is poor evidence of a weak association (OR<2.0) between COPD and oral health (II-2/3, grade C recommendation). 3) There is good evidence (I, grade A recommendation) that improved oral hygiene and frequent professional oral health care reduces the progression or occurrence of respiratory diseases among high-risk elderly adults living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
417
0
58

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 559 publications
(493 citation statements)
references
References 40 publications
(62 reference statements)
6
417
0
58
Order By: Relevance
“…Good oral health and regular professional dental cleaning has improved respiratory outcomes for patients, particularly those living in nursing homes. A recent meta-analysis has shown that periodontal disease may be associated with COPD [30]. As a large proportion of inhaled drugs are retained in the oral cavity, they may also interfere with oral physiology and the oral microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Good oral health and regular professional dental cleaning has improved respiratory outcomes for patients, particularly those living in nursing homes. A recent meta-analysis has shown that periodontal disease may be associated with COPD [30]. As a large proportion of inhaled drugs are retained in the oral cavity, they may also interfere with oral physiology and the oral microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the aggravation of periodontal disease, there is a bidirectional causality between some diseases of the oral cavity and systemic morbidities, such as cardiovascular and respiratory diseases 11,13,[25][26] . The presence of oral biofilm in these patients could trigger an inflammatory response, causing a significant increase in the quantity of immunoglobulin and circulating chemical mediators of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…During hospitalization, patients often neglect themselves, feel discouraged and even become physically or mentally incapacitated, and this may adversely affect their performance of oral hygiene care [2][3][4][5][6][7][8][9] . Oral hygiene negligence facilitates the accumulation of microorganisms in the form of biofilm, the etiological agent of oral conditions such as caries and periodontal disease 8,[10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, there is evidence for direct links between oral health and general health. Systematic reviews concluded that poor oral hygiene and periodontal disease are risk factors for pneumonia, and possibly also for chronic obstructive pulmonary disease (Azarpazhooh and Leake 2006;Sjögren et al 2008), and that periodontal disease adversely affects diabetes outcomes (Borgnakke et al 2013). …”
Section: Introductionmentioning
confidence: 99%